Zdravljenje bakterijskih okužb urogenitalnega trakta - Kerec Kos, Mojca (Farmacevtski vestnik, 2011)
Urinary tract infections are the most commonly occurring bacterial infections and they occur more frequently in females. The goals of treatment of urinary tract infections are to prevent or treat systemic consequences of the infections, eradicate the invading organisms and prevent the recurrence of infection. Genital bacterial infections are in most cases sexually transmitted and often associated with infertility or ectopic pregnancy. In the article the guidelines for outpatient treatment of bacterial urogenital infections are presented as well as the properties of the most important drugs involved in treatment.
Keywords: antibiotic; antibiotiki; okužbe sečil; protimikrobne učinkovine; therapy; urogenitalne infekcije; zdravljenje